1990
DOI: 10.1161/01.cir.81.4.1331
|View full text |Cite
|
Sign up to set email alerts
|

Mean transit time for the assessment of myocardial perfusion by videodensitometry.

Abstract: The intrinsic limitations of coronary arteriography to predict the physiological effects of coronary obstructions are well known. Therefore, more direct assessments of the functional significance of coronary stenoses are becoming increasingly important. Study of contrast passage by electrocardiogram-triggered digital radiography has been proposed as a way of assessing changes in myocardial perfusion. The main problems in this approach are the limited time for motionless image acquisition, the potential alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 43 publications
1
40
0
1
Order By: Relevance
“…Several previous studies have evaluated coronary blood flow by using angiographic images. Pijls et al (40,41,42) measured the mean transit time for the assessment of myocardial perfusion by videodensitometry. Molloi et al (35,37) have shown that the FPA analysis technique can be used to measure absolute coronary blood flow by analyzing the propagation of a contrast material signal in the coronary system.…”
Section: Protocolmentioning
confidence: 99%
“…Several previous studies have evaluated coronary blood flow by using angiographic images. Pijls et al (40,41,42) measured the mean transit time for the assessment of myocardial perfusion by videodensitometry. Molloi et al (35,37) have shown that the FPA analysis technique can be used to measure absolute coronary blood flow by analyzing the propagation of a contrast material signal in the coronary system.…”
Section: Protocolmentioning
confidence: 99%
“…7 Coronary angiographic video densitometry has been evaluated in patent vessels using the mean transit time of contrast clearance to assess myocardial perfusion, according to the principles of indicator dilution theory. 8 Based on these considerations, we sought to develop a more exact, inexpensive, and easy to apply angiographic method for characterising coronary collaterals. Our aim in this study was to test the hypothesis that the time to clearance or washout of radiographic contrast medium trapped distal to an occluded collateral receiving vessel is inversely related to collateral flow, and that this provides an accurate method of characterising coronary collaterals (figs 1 and 2).…”
mentioning
confidence: 99%
“…In most previous studies [Pijls 1990] [Korosoglou 2007], myocardial ROI was smaller than in our method. We have chosen to include the whole distribution bed of the infarct-related vessel in the ROI because the distribution of contrast material in the myocardium is usually not homogeneous.…”
Section: Application Of Our Computerized Methods In Stemi Patientsmentioning
confidence: 77%
“…Pijls et al used least squares minimization with gammadistribution function [Pijls 1990]. A two-compartment mathematical model was also proven to be useful for regional perfusion assessment in a canine model [Eigler 1989] and later in humans [Schühlen 1994].…”
Section: Application Of Our Computerized Methods In Stemi Patientsmentioning
confidence: 99%
See 1 more Smart Citation